Senso del colore e assenza di colori nell’architettura sacra medievale e nelle sue ‘rivisitazioni’ in Italia: qualche considerazione sulla facies esterna - Fachechi, Grazia Maria (Opus Incertum, 2017)
As Michael Pastoureau contends, the Middle Ages was the era of colour, when many things had the “right to colour”. Things that would not be polychrome anymore in the modern and contemporary age, such as building facades and sculptures (he says so, but of course it is just a generalization), which will instead conform to a purely monochromatic, often totally white, aesthetic. Though during the Middle Ages a polychromatic appearance of buildings and sculptures was usually preferred, we have extraordinary examples of Cistercian buildings where colour was programmatically refused (even stained glass windows were in grisaille), which influenced modern and contemporary architects, such as Le Corbusier. So, we can say that the Middle Ages continued and strengthened the relationship between form and colour which characterized the temples and sculptures of Antiquity. Even though studies on polychromy in Medieval monuments have recently become more common, we still lack a critical overview that, based on single case studies, can interpret the data and answer the questions: what was the "chromatic approach" of the Medieval architect, and how did he express it?